Determinants of Compliance for Breast and Cervical Cancers Screening among Female Police Personnel of Mumbai, India—A Cross-Sectional Study - Kulkarni, Vasundhara Y.; Mishra, Gauravi A.; Pimple, Sharmila A.; Patil, Anil S.; Bajpai, Jyoti; TS, Shylasree (Indian Journal of Medical and Paediatric Oncology, 2022)
Introduction Women working in police force have unique and vital role to play in law enforcement. Although these women have established a secured place for themselves in the police force, they are exposed to several behavioral and health risks apart from job stress. All these can have potentially serious consequences on their well-being.Objectives To determine the compliance to breast and uterine cervical cancers screening and identify predictors of participation in breast and cervical cancers screening among women police personnel.Materials and Methods This is a cross-sectional study conducted among the Mumbai police personnel during the period 2019 to 2021. All women working for Mumbai police work force in 12 zones were invited to participate in the study. Temporary clinics for screening were set up in different police stations and eligible participants were enrolled after obtaining written informed consent. This was followed by sociodemographic and risk factor assessment, health education program, screening for common cancers conducted by trained primary health workers (breast by clinical breast examination and uterine cervix by visual inspection with 5% acetic acid). Screen positives were referred according to predefined referral criteria for further investigations and management.Results A total of 3,017 police women were contacted, among them, 2,629 (87.14%) were eligible for screening, 2,609 (99.24%) participated in health education, and 1,839 (69.95%) complied for breast or cervical cancer screening. Further, compliance for screening of breast and uterine cervix were 1,837 (91.67%) and 1,297 (64.72%). A total of 256 (13.94%) and 217 (11.81%) police women were screen positives for breast and cervical cancers. According to multivariate logistic regression analysis, women younger than 50 years, those who were not married or were widowed or separated, postmenopausal women, and those who did not have shift duties had higher compliance for breast and cervix cancers screening.Conclusion Good participation for breast and cervical cancers screening was seen among the women police personnel. This study has demonstrated that awareness and screening by simple low-cost methods for breast and cervical cancers screening is easily implementable and can be replicated among the women police force in different states of India.
Keywords: screening; breast cancer; uterine cervix cancers; police